A Case of Large Gastric Trichobezoar: Case Report and Review of Literature - Lamanna, Anthony; Sidhu, Ankur; Foo, Jonathan; Aly, Ahmad (Archives of Clinical and Medical Case Reports, 2018)
Trichobezoars are concretions of swallowed hair retained within the digestive tract, most commonly the stomach. They predominate in young females during childhood and adolescence and are usually associated with psychiatric illness. These usually develop insidiously and hence at presentation are large in size. In this report, we present a case of a young female patient with large 17.5 × 12.2 × 5 cm trichobezoar that had to be surgically removed.